When the State Tackles Family Law Issues: The Attitudes of Surabaya and Sidoarjo Religious Offices on Child Marriage, Sirri Marriage, and Domestic Violence - Rohman, Holilur; Rifqi, Muhammad Jazil (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2024)
This article explores how the Religious Offices in Surabaya and Sidoarjo implement preventive measures against child marriage, sirri marriage, and domestic violence—issues that have the highest incidence rates in East Java. Notably, only a limited number of Religious Offices have actively engaged in such preventive efforts. This study examines the implementation, challenges, and evaluation of these preventive measures through interviews with relevant stakeholders. The findings indicate that the preventive initiatives undertaken by the Religious Offices in Surabaya and Sidoarjo are to promote family well-being by fostering healthy family relationships in both thought and action, ensuring financial stability, upholding the principles of Islamic marriage, and protecting families from violence. These efforts seek to establish a stable family structure capable of raising future generations. [Artikel ini mengeksplorasi bagaimana Kantor Urusan Agama Surabaya dan Sidoarjo dalam melakukan pencegahan terkait perkawinan anak, nikah siri, dan KDRT. Pasalnya, tidak semua Kantor Urusan Agama mengimplementasikan pencegahan terkait isu-isu di atas. Kantor Urusan Agama di Surabaya dan Sidoarjo menjadi acuan utama penelitian ini. Penelitian ini sendiri mengkaji bagaimana pelaksanaan, tantangan, dan evaluasi pencegahan dari ketiga problematika tersebut dengan wawancara mendalam kepada para aparat Kantor Urusan Agama Surabaya dan Sidoarjo. Di simpulkan bahwa implementasi pencegahan yang dilaksanakan oleh Kantor Urusan Agama Surabaya dan Sidoarjo tidak lain adalah dengan mewujudkan keluarga sejahtera dengan mengatur pola hubungan keluarga yang baik dalam pemikiran dan tindakan. Fokus mereka adalah meningkatkan kemampuan dalam mengelola kebutuhan finansial, pemahaman terkait prinsip-prinsip perkawinan menurut Islam, serta menguatkan pemahaman para pasangan terkait tindakan anti kekerasan.]